Anti-Toxoplasma Effects of Dracocephalum Polychaetum Essential Oil - Khamesipour, Faham; Pourmohammad, Amirhossein; Jafarian-Dehkordi, Mohsen (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Toxoplasma gondii is a common parasitic disease with a cosmopolitan prevalence, causing severe health problems. Although chemotherapy for toxoplasmosis is readily available, most have side effects. Objectives. This study assesses the Dracocephalum polychaetum essential oil against T. gondii activity. In vitro, the anti-Toxoplasma effects of D. polychaetum essential oils with different concentrations were evaluated. Methods. In the present study, T. gondii RH strain tachyzoites were exposed to D. polychaetum essential oil, and their viability effect on the parasite was evaluated. The viability test of tachyzoites was performed by using the staining method trypan blue in vitro. The inhibitory effect of D. polychaetum extract on T. gondii RH strain tachyzoites in the Vero cell line was evaluated. Results. D. polychaetum has valuable efficacy in vitro, outperforming pyrimethamine and sulfadiazine at 30 and 90 minutes after exposure (p<0.05). D. polychaetum essential oil showed anti-Toxoplasma activity in the cell line (IC50: 241.7 μg/mL). After T. gondii-infected Vero cells had been incubated with different concentrations of the D. polychaetum essential oil, their viability decreased in a dose-dependent manner. Conclusions. In conclusion, D. polychaetum extract as an herbal medicine might be a valuable alternative to routine chemotherapy for toxoplasmosis.